Sodium hydride as a powerful reducing agent for topotactic oxide deintercalation: Synthesis and characterization of the nickel(I) oxide LaNiO2 - Hayward, M; Green, M; Rosseinsky, M; Sloan, J (1999)
The capability of sodium hydride as a reducing agent in oxide deintercalation reactions is explored. The Ni(III) perovskite LaNiO3 can be reduced topotactically to LaNiO2, isostructural with the 'infinite layer' cuprates, using solid sodium hydride in a sealed evacuated tube at 190 ≤ T/°C ≤ 210, and a similar infinite-layer phase is prepared by reduction of NdNiO3. Structural characterization indicates the coexistence of incompletely reduced regions, with five-coordinate Ni centers due to the introduction of oxide anions between the NiO23- sheets, giving samples with a refined stoichiometry of LaNiO(2.025(3)). Neutron powder diffraction and magnetization measurements indicate that the lamellar Ni(I) phase does not show the long-range antiferromagnetic ordering characteristic of isoelectronic Cu(II) oxides. This may be due either to the influence of the interlamellar oxide defect regions or to the reduced covalent mixing of Ni 3d and O 2p levels.